Antiplatelet strategy for patients with acute coronary syndrome and chronic kidney disease: a systematic review and meta-analysis - Li, Siqi; Wang, Dayang; Han, Xiaowan; Zhang, Diying; Deng, Hongxiao; Pan, Guozhong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPatients with both acute coronary syndrome (ACS) and chronic kidney disease (CKD) face heightened risks of adverse cardiovascular events and bleeding. An optimal antiplatelet strategy for this patient population is needed.MethodsWe conducted a systematic review and meta-analysis to evaluate comparative advantages of clopidogrel vs. ticagrelor in the choice of dual antiplatelet therapy (DAPT) strategies for patients with ACS combined with CKD, while also exploring the appropriate duration of DAPT in the presence of CKD. Relevant studies were retrieved from PubMed, Embase, Cochrane Library, and Web of Science. The primary outcomes were all-cause mortality, major adverse cardiovascular events (MACE), and major bleeding. Data were analyzed using RevMan 5.4.1, and STATA 14 was used to assess publication bias. This study was registered with PROSPERO (CRD42024593764).ResultsSix studies involving 9,947 patients met the inclusion criteria. Compared with clopidogrel, ticagrelor was associated with a reduced risk of MACE (RR: 0.89, 95% CI: 0.80–0.99; P = 0.04) and stroke (RR: 0.66, 95% CI: 0.45–0.96; P = 0.03) in patients receiving DAPT. No significant differences were observed in all-cause mortality, major bleeding, cardiovascular death, or acute myocardial infarction. Three studies on DAPT duration showed a consistent trend, indicating that shortening DAPT duration did not benefit patients.ConclusionsIn patients with ACS combined with CKD, ticagrelor-based DAPT has advantages over clopidogrel-based DAPT, which is associated with a lower incidence of MACE. And shortening the duration of DAPT does not improve clinical outcomes.